THE COMPARATIVE BETWEEN JIGSAW COOPERATIVE LEARNING MODEL AND QUANTUM LEARNING ON MATHEMATICS LEARNING OUTCOMES - Nur Hasanah; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Mastery and understanding the mathematical concept is one thing that is very important to achieve learning outcomes. However, this cannot be achieved the maximum. Therefore requires learning alternatives include using Cooperative Jigsaw and Quantum Learning for mathematics. This type of research is a comparative study. The study population all seventh-grade students of State Junior High School (SMPN) 01 Kretek Academic Year 2015/2016. The research sample is student’s class VIIC and VIID. The sampling technique used random sampling of classes. Methods of data collection using the test. The research instrument includes validity, reliability, level of difficulty, and distinguishing matter. Analysis of the data used t-test. The results showed significant differences between student learning mathematics learning using Jigsaw Cooperative models with student learning to use Quantum Learning. Based on data analysis, , which means the Cooperative Jigsaw learning model is more effective than the learning model Quantum Learning on students mathematics learning outcomes.